ID 224 – Patterns of thalamic oscillatory activity in patients with parkinsonian tremor and essential tremor. Issue 3 (March 2016) - Zhuang, P.; Hallett, M.; Liu, T.-T.; Zhang, Y.-Q.; Li, J.-Y.; Li, Y.-J.
Abstract : Objective: To explore oscillatory activity in the ventrolateral thalamus in patients with parkinsonian tremor and essential tremor (ET). METHODS: 26 PD patients and 14 ET patients who underwent thalamic surgery were studied. Neuronal activity in the Vop/Vim and EMG of limbs were recorded. Single unit analysis and ISI histograms were performed. Spectral analysis and Coherence analysis were carried out.RESULTS: Of 125 oscillatory neurons obtained from PD, 74.4% ( n  = 93) were tremor frequency oscillatory neurons (4.5 ± 0.9 Hz, TFB); 25.6% ( n  = 32) were ß frequency oscillatory neurons (16.6 ± 8.9 Hz, ßFB). Of 46 oscillatory neurons obtained from ET, 89.1% ( n  = 41) were TFB oscillatory neurons (6.8 ± 4.5 Hz); 10.9% ( n  = 5) were ßFB oscillatory neurons. The proportion of ßFB oscillatory neurons in PD were higher than that of neurons in ET ( p  < 0.05). MSFR of oscillatory neurons in PD were lower than that of neurons in ET (26.7 ± 6.8 Hz vs. 42.3 ± 15.6 Hz, p  < 0.05). Conclusions: The data support the notion that ßFB oscillatory neurons are associated with dopaminergic deficits in the basal ganglia in PD. Compared with normal MSFR (estimated to be 30 Hz in normal monkeys), the MSFR of oscillatory neurons in the VL are likely high in ET suggesting an etiologic role of the thalamus in ET.